2020
DOI: 10.1007/s12274-020-3158-1
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic, photo-sterilize, and reusable mask based on graphene nanosheet-embedded carbon (GNEC) film

Abstract: The 2019 coronavirus disease (COVID-19) has affected more than 200 countries. Wearing masks can effectively cut off the virus spreading route since the coronavirus is mainly spreading by respiratory droplets. However, the common surgical masks cannot be reused, resulting in the increasing economic and resource consumption around the world. Herein, we report a superhydrophobic, photo-sterilize, and reusable mask based on graphene nanosheet-embedded carbon (GNEC) film, with high-density edges of standing structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 39 publications
(37 reference statements)
0
66
0
1
Order By: Relevance
“…S14 ). Such temperature is much lower than the recently reported bioprotective materials (60–110 °C) for microbial inactivation through only photothermal effect [ [47] , [48] , [49] ], nevertheless, it is sufficient to serve as an adjuvant role for the pathogen inhibition by accelerating the dehydration of pathogenic droplets and aerosols, without causing discomfort in contact with mouth and skin.…”
Section: Resultsmentioning
confidence: 83%
“…S14 ). Such temperature is much lower than the recently reported bioprotective materials (60–110 °C) for microbial inactivation through only photothermal effect [ [47] , [48] , [49] ], nevertheless, it is sufficient to serve as an adjuvant role for the pathogen inhibition by accelerating the dehydration of pathogenic droplets and aerosols, without causing discomfort in contact with mouth and skin.…”
Section: Resultsmentioning
confidence: 83%
“…In another work, a superhydrophobic, photo-sterilize, and reusable mask based on a graphene nanosheet-embedded carbon (GNEC) film exhibits high hydrophobicity (water contact angle: 157.9°) and filtration efficiency [with 100% bacterial filtration efficiency (BFE)]. 123 In addition, the GNEC mask presents a photo-sterilize ability to being heated up to 110 °C quickly under the solar illumination, which provides promising potential for further investigation.…”
Section: Antiviral Coatings Against Sars-cov-2mentioning
confidence: 99%
“…Though previous studies showed that the graphene materials exhibited outstanding antibacterial activity under sunlight and proposed that the high temperature (e.g., 110 °C) resulted from photothermal effect might inactivate virus, there was no direct evidence on how effective the antiviral efficacy could be achieved. [ 27–29 ] In addition, such a high temperature could impractical in real scenario as the solar irradiance is often lower. Here we report that laser‐induced graphene (LIG) and its composites [ 30–32 ] show excellent antiviral activity against HCoV‐OC43 and HCoV‐229E, two human coronaviruses serving as surrogates for SARS‐CoV‐2.…”
Section: Introductionmentioning
confidence: 99%